Human antigen‐specific CD4+CD25+CD134+CD39+ T cells are enriched for regulatory T cells and comprise a substantial proportion of recall responses. Issue 6 (29th April 2014) - Seddiki, Nabila; Cook, Laura; Hsu, Denise C.; Phetsouphanh, Chansavath; Brown, Kai; Xu, Yin; Kerr, Stephen J.; Cooper, David A.; Munier, C. Mee Ling; Pett, Sarah; Ananworanich, Jintanat; Zaunders, John; et al.
<x xml:space="preserve">Abstract</x> Human Ag‐specific CD4+ T cells can be detected by their dual expression of CD134 (OX40) and CD25 after a 44 hours stimulation with cognate Ag. We show that surface expression of CD39 on Ag‐specific cells consistently identifies a substantial population of CD4+CD25+CD134+CD39+ T cells that have a Treg‐cell‐like phenotype and mostly originate from bulk memory CD4+CD45RO+CD127lowCD25highCD39+ Treg cells. Viable, Ag‐specific CD25+CD134+CD39+ T cells could be expanded in vitro as cell lines and clones, and retained high Forkhead Box Protein 3, CTLA‐4 and CD39 expression, suppressive activity and Ag specificity. We also utilised this combination of cell surface markers to measure HIV‐Gag responses in HIV+ patients before and after anti‐retroviral therapy (ART). Interestingly, we found that the percentage of CD39− cells within baseline CD4+ T‐cell responses to HIV‐Gag was negatively correlated with HIV viral load pre‐ART and positively correlated with CD4+ T‐cell recovery over 96 weeks of ART. Collectively, our data show that Ag‐specific CD4+CD25+CD134+CD39+ T cells are highly enriched for Treg cells, form a large component of recall responses and maintain a Treg‐cell‐like phenotype upon in vitro expansion. Identification and isolation of these cells enables the role of Treg cells in memory responses to be further defined and provides a development pathway for novel therapeutics.